Refining centromedian nucleus stimulation for generalized epilepsy with targeting and mechanistic insights from intraoperative electrophysiology - Jonathan C. Ho; Thandar Aung; Arianna Damiani; Lilly Tang; Arka N. Mallela; Donald J. Crammond; Jorge A. González-Martínez (Nature Communications)
Abstract Epilepsy affects 65 million people worldwide, with 30% suffering from drug-resistant epilepsy. While surgical resection is the primary treatment, its application is limited in generalized epilepsy. Centromedian nucleus neurostimulation offers a promising alternative, yet its mechanisms remain unclear, limiting target optimization. We present a multimodal approach integrating intraoperative thalamic and sub-scalp electroencephalogram recordings with post-implant reconstructions to define neural targets affected by centromedian nucleus stimulation. We find that stimulating low-activity regions near the centromedian nucleus, particularly the white matter of internal medullary lamina, induces significant cortical delta power increases greater than stimulation within high-activity areas inside the nucleus. Implantation in these low-activity targets results in greater than 50% seizure reduction in all three subjects. These findings suggest that seizure control primarily involves stimulating white matter regions such as the internal medullary lamina rather than the centromedian nucleus itself. A personalized, electrophysiology-guided implantation approach may enhance neurostimulation efficacy in drug-resistant epilepsy.